Extracellular Vesicles Are Key Regulators of Tumor Neovasculature - Kuriyama, Naoya; Yoshioka, Yusuke; Kikuchi, Shinsuke; Azuma, Nobuyoshi; Ochiya, Takahiro (Frontiers in Cell and Developmental Biology, 2020)
Tumor progression involves a series of biologically important steps in which the crosstalk between cancer cells and the surrounding environment is an important issue. Angiogenesis is a key tumorigenic phenomenon for cancer progression. Tumor-related extracellular vesicles (EVs) modulate the tumor microenvironment (TME) through cell-to-cell communication. Tumor cells in a hypoxic TME release more EVs than cells in a normoxic environment due to uncontrollable tumor proliferation. Tumor-derived EVs in the TME influence endothelial cells (ECs), which then play multiple roles, contributing to tumor angiogenesis, loss of the endothelial vascular barrier by binding to ECs, and subsequent endothelial-to-mesenchymal transition. In contrast, they also indirectly induce tumor angiogenesis through the phenotype switching of various cells into cancer-associated fibroblasts, the activation of tumor-associated ECs and platelets, and remodeling of the extracellular matrix. Here, we review current knowledge regarding the involvement of EVs in tumor vascular-related cancer progression.